Test estandarizados y sus resultados en la licenciatura en educación básica - Chacón Benavides, José Antonio; Moreno Pinzón, Israel Alfonso; Fonseca Correa, Luis Ángel (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Introduction: The research analyzes the differences in the results of the Higher Education Quality Examinations (ECAES) of students in 2011 of the degree in Basic Education with emphasis in mathematics, humanities and Spanish lan- guage of distance modality with Virtual support of the Faculty of Distance Studies. Methodology: Databases were downloaded from the results of the program tests, from the FTP-ICFES system and operated with numerical scores, the name of the race, the modality with virtual support of its students, the degree in Education Basic. Results: it is evident that there are no significant gaps in the results of the Generic Components modules since in most of the modules it is above the average of the reference group Education and below the National average. Conclusions: We ve- rified the differences between the results of the students of the program according to the established modules and it is necessary to reformulate through Pedagogical, methodological and Didactic strategies in the training of the Graduates in Basic Education, with a view to strengthening the competences Related to the Teaching, Evaluating and Training of the graduates so that the professional program in the field of education can improve the preparation process by the students.